2023
DOI: 10.3389/fnut.2023.1123422
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a novel hydrolase-producing probiotic Bacillus licheniformis and its application in the fermentation of soybean meal

Abstract: Soybean meal (SBM) is one of the most important sources of plant-based protein in the livestock and poultry industry. However, SBM contains anti-nutritional factors (ANFs) such as glycinin, β-conglycinin, trypsin inhibitor and phytic acid that can damage the intestinal health of animals, inevitably reducing growth performance. Fermentation using microorganisms with probiotic potential is a viable strategy to reduce ANFs and enhance the nutritional value of SBM. In this study, a novel potential probiotic Bacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…According to the authors, B. licheniformis MVS1 exhibited the highest cellulase activity (0.120 ± 0.012 IU/mL) when wheat straw was the Cellulase has been associated with improvements in bread, particularly those with a high dietary fiber content [64,65]. It has been described that the presence of peptidases and cellulases of B. licheniformis isolated from camel feces can reduce allergenic compounds and improve the nutrition properties of soybean meal, which is a source of protein for animal feeds [66]. B. licheniformis MVS1 and Bacillus sp.…”
Section: Qualitative and Quantitative Hydrolases Analysismentioning
confidence: 99%
“…According to the authors, B. licheniformis MVS1 exhibited the highest cellulase activity (0.120 ± 0.012 IU/mL) when wheat straw was the Cellulase has been associated with improvements in bread, particularly those with a high dietary fiber content [64,65]. It has been described that the presence of peptidases and cellulases of B. licheniformis isolated from camel feces can reduce allergenic compounds and improve the nutrition properties of soybean meal, which is a source of protein for animal feeds [66]. B. licheniformis MVS1 and Bacillus sp.…”
Section: Qualitative and Quantitative Hydrolases Analysismentioning
confidence: 99%
“…There is an increasing evidence that lactic acid bacteria have the ability to degrade proteins during fermentation and lactic acid bacteria with high intestinal adhesion also have antibacterial properties (Ma et al ., 2022). Antioxidant, anti‐inflammatory and antihypertensive activities were also found in fermented soybean meal (Cui et al ., 2020; Yao et al ., 2021; Qi et al ., 2023). Further research has shown that the fermented soybean meal can improve intestinal barrier function and reduce inflammation of piglets, which is more suitable for poultry feed and aquaculture (Cheng et al ., 2019a).…”
Section: Microbial Fermentation Of Soybean Mealmentioning
confidence: 99%
“…Bacillus licheniformis is the dominant bacterium involved in the fermentation of Tibetan tea. It is a probiotic bacterium with high-temperature tolerance; it can grow in a high-temperature environment and possesses phytase, protease, cellulase, and xylanase activities (Qi et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%